PENGARUH PENERAPAN STRATEGI PEMODELAN TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PAI KELAS VII SMPN 8 PAMEKASAN - Rosa Agustina Sari Rosa; Ach. Sya'roni (Journal of Education Partner, 2022)
There are two issues that are the main studies in this study, first, Is the Effect of The Application of The Strategy of Learning To Student Learning On The Motivation of Learning Students in The Subjects of Islamic Religious Education in SMPN 8 Pamekasan?, secondly How Much Influence of Modeling Learning Strategies On Student Learning Motivation Of Islamic Religious Education Subjects in SMPN 8 Pamekasan. This research approach uses a quantitative approach, with a correlational type. The instruments used in data collection are questionnaires, interviews, observations and documentation. The results showed that: 1). There is an effect of The Application of Modeling Learning Strategies On Student Learning Motivation Of Islamic Religious Education Subjects in SMPN 8 Pamekasan. This is evident from the results of the analysis of data obtained at 0.87 out of 30 samples. This figure turns out to be greater than the price of the "r" product moment table criticism in both the 5% and 1% confidence intervals where N-nr = 30-2 = 28 is obtained values of 0.399 at the signification level of 5% and 0.497 at the signification level of 1%. 2) The Effect of The Application of Modeling Learning Strategies On Student Learning Motivation Of Islamic Religious Education Subjects in SMPN 8 Pamekasan belongs to the high category. This shows that the Effect of Applying Modeling Learning Strategies on Student Learning Motivation in SMPN 8 Pamekasan is in the range of numbers between 0.70 to 0.90 with high categories. Based on the results of the above research, the Application of Modeling Learning Strategies against Student Learning Motivation of Islamic Religious Education Subjects in SMPN 8 Pamekasan is the right way to get overall and individual class participation.